Analysis of Factors Affecting Poverty in The Province of The Bangka Belitung Islands - Aprillia, Anggi; Wardhani, Rulyanti Susi; Akbar, Muhammad Faisal (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
Poverty is a condition of the inability of individuals or community groups to meet basic needs such as housing, clothing and food to ensure a certain standard of living. If a country is able to reduce the level of poverty, then the welfare of the community can be realized through the implementation of quality development. This study aims to analyze and determine the effect of economic growth, income inequality, government spending and the open unemployment rate on poverty. This research used quantitative research. The analytical tool used in this study is multiple linear regression with panel data. The results showed that partially the economic growth had a negative and significant effect on poverty, government spending had a negative and insignificant effect on poverty and income inequality and open unemployment had a positive and significant effect on poverty in the Province of the Bangka Belitung Islands. Meanwhile, the results of the simultaneous test show that overall the variables of economic growth, income inequality, government spending and the open unemployment rate have a positive and significant effect on poverty in the Province of the Bangka Belitung Islands. Keywords: Economic Growth, Income Inequality, Government Expenditure, Unemployment Rate, Poverty JEL: O40, 015, H53, I30